2012
DOI: 10.1039/c2nr11743f
|View full text |Cite
|
Sign up to set email alerts
|

Redox-switchable devices based on functionalized graphene nanoribbons

Abstract: The possibility of tuning the electronic properties of graphene by tailoring the morphology at the nanoscale or by chemical functionalization opens interesting perspectives towards the realization of devices for nanoelectronics. Indeed, the integration of the intrinsic high carrier mobilities of graphene with functionalities that are able to react to external stimuli allows in principle the realization of highly efficient nanostructured switches. In this paper, we report a novel approach to the design of rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…For instance, Selli et al have proposed redox-switchable devices in a recent work, where controlling of aromaticity patterns with different functional groups at the edge enables the switching behaviour. 34 GNRs belong to a new class of one-dimensional materials whose edges are easily accessible to chemical functionalisation as a suitable way to modify their properties. 14,34 In this regard, hydrogen termination of dangling bonds is the usual approach in molecular modelling of carbon nanomaterials, but other types of edge functionalisation are equally accessible to computational chemistry and it provides valuable data concerning the chemical modification of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Selli et al have proposed redox-switchable devices in a recent work, where controlling of aromaticity patterns with different functional groups at the edge enables the switching behaviour. 34 GNRs belong to a new class of one-dimensional materials whose edges are easily accessible to chemical functionalisation as a suitable way to modify their properties. 14,34 In this regard, hydrogen termination of dangling bonds is the usual approach in molecular modelling of carbon nanomaterials, but other types of edge functionalisation are equally accessible to computational chemistry and it provides valuable data concerning the chemical modification of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…At low target coverages (about 0.68 mol nm −2 , corresponding to 68 molecules on the equilibrated graphene substrate of about 10 × 10 nm), simulations of the formation of the interface between PTCDI‐C13 and graphene, carried out with the pristine interaction potential ( μ = 1) in kinetic conditions (see Table S1, Supporting Information), show a clear propensity to formation of disordered molecular aggregates in the flat‐lying configurations ( γ = 90°, see Figure S2, Supporting Information). The occurrence of the flat‐lying configuration, favored by the π‐stacking interactions between the PTCDI‐C13 core and the underlying honeycomb lattice with partial aromatic character, has been largely observed in the growth of perylene derivatives on graphitic substrates at low coverages . At the same coverage, aggregation in thermodynamic conditions (see Table S1, Supporting Information) induces long‐range ordering at the interface, leading to a closely packed (herringbone‐like) planar interfacial layer (IL) of PTCDI‐C13 molecules on graphene, as shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“…[ 203,204 ] Recent research work has demonstrated the potential of low‐dimensional carbon nanostructures, such as graphene, carbon nanotubes, or composites, to realize highly conductive and transparent electrodes for solar cells. [ 205,206 ]…”
Section: Methodsmentioning
confidence: 99%
“…[203,204] Recent research work has demonstrated the potential of low-dimensional carbon nanostructures, such as graphene, carbon nanotubes, or composites, to realize highly conductive and transparent electrodes for solar cells. [205,206] Nevertheless, wet processes can unleash their full potential in the fabrication of electrodes based on organic molecular or polymer materials. The relatively low conductivity of organic materials is usually alleviated by doping the electrode, a process that, however, can limit the stability of the device.…”
Section: Charge Extracting Electrodesmentioning
confidence: 99%